2014
DOI: 10.3892/ijo.2014.2779
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile for predicting survival of patients with meningioma

Abstract: Abstract. Current staging methods are inadequate for predicting the overall survival of meningioma. DNA microarray technologies improve the understanding of tumour progression. We analysed genome wide expression profiles of 119 meningioma samples from two previous published DNA microarray studies. The Cox proportional hazards regression models were applied to identify overall survival related gene signature. A total of 449 genes (109 upregulated and 340 downregulated) were identified as differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Microarray gene expression analysis has identified potential biomarkers to distinguish benign meningiomas from those with higher risk of progression or recurrence. A 37-gene signature was identified to correlate well with overall survival, 74 and recently an 18-gene signature was found to correlate with progression-free survival after validation in an independent cohort. 75 These genes were found to be involved in pathways involving normal embryonic development, cell proliferation/invasion, and angiogenesis, among others.…”
Section: Transcriptomic Signatures In Meningiomamentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray gene expression analysis has identified potential biomarkers to distinguish benign meningiomas from those with higher risk of progression or recurrence. A 37-gene signature was identified to correlate well with overall survival, 74 and recently an 18-gene signature was found to correlate with progression-free survival after validation in an independent cohort. 75 These genes were found to be involved in pathways involving normal embryonic development, cell proliferation/invasion, and angiogenesis, among others.…”
Section: Transcriptomic Signatures In Meningiomamentioning
confidence: 99%
“…In addition to this, increased transglutaminase 2 (TGM2) expression has been described in higher-grade meningioma 76 and the deleted in colorectal cancer (DCC) gene, which encodes a transmembrane receptor for netrin-1 and has also been suggested to be a marker for risk of meningioma progression. 77 Most gene expression studies have been limited by their small sample size (10-50 tumors), with minimal overlap in the candidate genes identified between studies, 64,74,[76][77][78][79][80] and therefore further studies are needed to validate potential gene expression biomarkers.…”
Section: Transcriptomic Signatures In Meningiomamentioning
confidence: 99%
“…The authors concluded that the development of recurrent meningiomas after gross total tumour resection is usually due to regrowth of the primary tumour and rarely to the emergence of an unrelated meningioma. A prognostic signature for meningioma prognosis was reported by Chen et al [ 27 ] who analysed genome wide expression profiles of 119 meningioma samples from two previously published DNA microarray studies [ 17 , 28 ] using the Cox proportional hazards regression models and found 37 genes to be specifically related to meningioma overall survival.…”
Section: Epidemiology and Histopathological Classificationmentioning
confidence: 99%
“…Genomics microarray, a high-throughput platform, represents a great powerful technology to analyze gene expression comprehensively [ 22 , 23 ]. In combination with multiple bioinformatics analyses, microarray technology has been widely valued as a tool with great promise to obtain gene signals during tumor process, drug resistance, and verify prognostic biomarkers in cancers [ 24 26 ]. Detection and verification of vital targets of drug resistance by using microarray analysis is a novel research strategy and may in favor of uncovering the underlying mechanisms of drug resistance.…”
Section: Introductionmentioning
confidence: 99%